Comparative Effects of Various Forms of Selenium on Thioredoxin Reductase Activity in Broiler Chickens - Gowdy, K.M.; Edens , F.W.; Mahmoud, K.Z. (International Journal of Poultry Science, 2015)
An experiment was conducted to measure thioredoxin reductase (TrxR) and glutathione peroxidase (GSH-Px) enzymatic activity in organs and TrxR activity in liver subcellular fractions in young broiler chickens. Broilers were fed either a (1) Control basal diet (no supplemental selenium but with a background level of 0.095 mg/kg) or diets providing supplemental selenium at 0.3 mg/kg as either (2) sodium selenite (SE; inorganic selenium), (3) Sel-Plex® (SY; organic selenium yeast), or (4) a combination (SS) of 0.15 mg/kg of both selenium forms. GSH-Px (measured in liver only) and TrxR activities were elevated by selenium, regardless of dietary form, in each organ examined. The TrxR activities in subcellular fractions were greatest in the mitochondrial lysate, nuclear pellet and post-mitochondrial supernatant, respectively and the lowest activity was associated with the mitochondrial pellet. Aurothioglucose (ATG; 0.1 μM/g BW) inhibited hepatic cell GSH-Px activity by more than 30% and TrxR activity by more than 80%, but glutathione reductase was not affected. The TrxR enzyme in the chicken might be different from the mammalian enzyme.